Antibiotic treatment for the sexual partner of women with Bacterial Vaginosis (Protocol) (2016)
Abstract. Bacterial vaginosis (BV) is an infection that has a prevalence between 10% to 50% worlwide. BV results in an imbalance of the normal vaginal flora. Microorganisms associated with BV have been isolated from the normal flora of the male genital tract, and their presence could be related to the recurrence of BV after antibiotic treatment. Therefore, the treatment of sexual partners could decrease the recurrence of infection and possibly the burden of the disease. The objective of the revision was to assess the effectiveness in women and the safety in men of concurrent antibiotic treatment for the sexual partners of women treated for BV. Seven RCTs (1026 participants) met our inclusion criteria, and pharmaceutical industry funded four of these trials. Based on high quality evidence, antibiotic treatment does not increase the rate of clinical or symptomatic improvement in women during the first week (risk ratio (RR) 0.99, 95% confidence interval (CI) 0.96 to 1.03; RR 1.06, 95% CI 1.00 to 1.12, respectively), between the first and fourth week (RR 1.02, 95% CI 0.94 to 1.11; RR 0.93, 95% CI 0.84 to 1.03, respectively) or after the fourth week (RR 0.98, 95% CI 0.90 to 1.07; RR 1.03, 95% CI 0.90 to 1.17, respectively). With low quality evidence antibiotic treatment does not led to a lower recurrence during the first and fourth week (RR 1.28, 95% CI 0.68 to 2.43) or after the fourth week of treatment (RR 1.00, 95% CI 0.67 to 1.52) in women, but increases the frequency of adverse events reported by sexual partners (RR 2.55, 95% CI 1.55 to 4.18).